African midwifery students' self-assessed confidence in antenatal care: a multi-country study. Issue 1 (1st January 2019) - Hildingsson, Ingegerd; Lindgren, Helena; Karlström, Annika; Christensson, Kyllike; Bäck, Lena; Mudokwenyu–Rawdon, Christina; Maimbolwa, Margaret C.; Laisser, Rose Mjawa; Omoni, Grace; Chimwaza, Angela; Mwebaza, Enid; Kiruja, Jonah; et al.
ABSTRACT: Background : Evidence-based antenatal care is one cornerstone in Safe Motherhood and educated and confident midwives remain to be optimal caregivers in Africa. Confidence in antenatal midwifery skills is important and could differ depending on the provision of education among the training institutions across Africa. Objective : The aim of the study was to describe and compare midwifery students' confidence in basic antenatal skills, in relation to age, sex, program type and level of program. Methods : A survey in seven sub-Saharan African countries was conducted. Enrolled midwifery students from selected midwifery institutions in each country presented selfreported data on confidence to provide antenatal care. Data were collected using a selfadministered questionnaire. The questionnaire consisted of 22 antenatal skills based on the competency framework from the International Confederation of Midwives. The skills were grouped into three domains; Identify fetal and maternal risk factors and educate parents; Manage and document emergent complications and Physical assessment and nutrition. Results : In total, 1407 midwifery students from seven Sub-Saharan countries responded. Almost one third (25-32%) of the students reported high levels of confidence in all three domains. Direct entry programs were associated with higher levels of confidence in all three domains, compared to post-nursing and double degree programs. Students enrolled at education with diploma level presented with high levels of confidence in two out of three domains. Conclusions : A significant proportion of student midwives rated themselves low on confidence to provide ANC. Midwifery students enrolled in direct entry programs reported higher levels of confidence in all domains. It is important that local governments develop education standards, based on recommendations from the International Confederation of midwives. Further research is needed for the evaluation of actual competence.